MicroRNA-3148 Modulates Allelic Expression of Toll-Like Receptor 7 Variant Associated with Systemic Lupus Erythematosus (2013)
We previously reported that the G allele of rs3853839 at 3′untranslated region (UTR) of Toll-like receptor 7 (TLR7) was associated with elevated transcript expression and increased risk for systemic lupus erythematosus (SLE) in 9,274 Eastern Asians [P = 6.5×10−10, odds ratio (OR) (95%CI) = 1.27 (1.17–1.36)]. Here, we conducted trans-ancestral fine-mapping in 13,339 subjects including European Americans, African Americans, and Amerindian/Hispanics and confirmed rs3853839 as the only variant within the TLR7-TLR8 region exhibiting consistent and independent association with SLE (Pmeta = 7.5×10−11, OR = 1.24 [1.18–1.34]). The risk G allele was associated with significantly increased levels of TLR7 mRNA and protein in peripheral blood mononuclear cells (PBMCs) and elevated luciferase activity of reporter gene in transfected cells. TLR7 3′UTR sequence bearing the non-risk C allele of rs3853839 matches a predicted binding site of microRNA-3148 (miR-3148), suggesting that this microRNA may regulate TLR7 expression. Indeed, miR-3148 levels were inversely correlated with TLR7 transcript levels in PBMCs from SLE patients and controls (R2 = 0.255, P = 0.001). Overexpression of miR-3148 in HEK-293 cells led to significant dose-dependent decrease in luciferase activity for construct driven by TLR7 3′UTR segment bearing the C allele (P = 0.0003). Compared with the G-allele construct, the C-allele construct showed greater than two-fold reduction of luciferase activity in the presence of miR-3148. Reduced modulation by miR-3148 conferred slower degradation of the risk G-allele containing TLR7 transcripts, resulting in elevated levels of gene products. These data establish rs3853839 of TLR7 as a shared risk variant of SLE in 22,613 subjects of Asian, EA, AA, and Amerindian/Hispanic ancestries (Pmeta = 2.0×10−19, OR = 1.25 [1.20–1.32]), which confers allelic effect on transcript turnover via differential binding to the epigenetic factor miR-3148.